2000
DOI: 10.1016/s0304-3959(99)00190-6
|View full text |Cite
|
Sign up to set email alerts
|

Parietal and cingulate processes in central pain. A combined positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) study of an unusual case

Abstract: Parietal, insular and anterior cingulate cortices are involved in the processing of noxious inputs and genesis of pain sensation. Parietal lesions may generate central pain by mechanisms generally assumed to involve the 'medial' pain system (i.e. medial thalamic nuclei and anterior cingulate cortex (ACC)). We report here PET and fMRI data in a patient who developed central pain and allodynia in her left side after a bifocal infarct involving both the right parietal cortex (SI and SII) and the right ACC (Brodma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 24 publications
4
58
1
4
Order By: Relevance
“…2A). We chose to stimulate the right hemisphere in our right-handed participants because evidence suggests that pain matrix is mainly lateralized to the right hemisphere, although networks across both hemispheres constitute the pain matrix (Casey, 1999;Peyron et al, 2000) irrespective of the side affected by pain (Borckardt et al, 2012;Symonds et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…2A). We chose to stimulate the right hemisphere in our right-handed participants because evidence suggests that pain matrix is mainly lateralized to the right hemisphere, although networks across both hemispheres constitute the pain matrix (Casey, 1999;Peyron et al, 2000) irrespective of the side affected by pain (Borckardt et al, 2012;Symonds et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Brain-specific mechanisms of experimentally induced acute pain have already been described in several studies, inter alia with the assistance of functional magnetic resonance imaging (fMRI), neuroelectrophysiological and neurosurgical procedures [1][2][3][4][5][6][7][8]. Structures involved in processing the multidimensional aspect of pain perception are often summarised with the term "pain matrix", and include several regions consistently found within investigations [1,8,9], hence accommodating the complex neurosignature pattern of pain [10].…”
Section: Insula-specific Responses Induced By Dental Pain a Proton Mmentioning
confidence: 99%
“…As noted above, a PET study of patients with Wallenburg strokes did not find activation of the ACC in response to stimuli which produced allodynia (Peyron et al, 1998), although such activation is often found in response to acute pain stimuli in healthy controls (Apkarian et al, 2005;Lenz et al, 2010). A combined PET and fMRI study of a unique patient with strokes of both the ACC and parietal cortex demonstrated cold allodynia, in the absence of hyperactivity in the remaining ACC (Peyron et al, 2000). In contrast, one fMRI study of a patient with CPSP resulting from a stroke of the posterolateral thalamus and adjacent internal capsule found activation of the ACC, the posterior parietal cortex, and the putamen during allodynia evoked by a cool stimulus (Seghier et al, 2005).…”
Section: Mechanisms Of Cold Allodynia In Patients With Central Painmentioning
confidence: 96%